Ultrasound surveillance in the high risk patient -does it deliver?. (18th April 2012) - Oniya, O; Ledingham, M; Duncan, A
Abstract : Background: Ultrasound surveillance remains one of the main stay in the management of the high risk antenatal patient. However, it contributes significantly to the burden of most Scan departments. The National institute for clinical excellence states that evidence does not support the routine use of ultrasound scanning after 24 weeks. Methodolgy: Retrospective Audit of fetal surveillance performed in a Teaching Hospital. Objectives: To assess how fetal surveillance scan assisted in the management of selected high risk patients. Results: 500 scans were performed in 202 patients. In 54.5% birth weights did not correlate with scan. Findings did not influence care in 78.2% and did not affect timing or mode of delivery in 86%. In 43 patients scan affected antenatal care. 15 patients had further scans. 6 had OGTT and 1 Gestational diabetes was diagnosed. 5 patients required admission. 26 women (13%) were delivered as a result of scan findings including 1 EMCS. 1 ECV was performed for undiagnosed breech presentation. 69% of babies with IUGR had not been picked up by scan. 38% of the 56 smokers had babies whose birth weight was on or below the 10 th centile. 75% of women scanned serially for booking late were of ethnic minority origin. Conclusion: Ultrasound surveillance is by no means infallible in the assessment of fetal wellbeing. Over half of estimated fetal weights as predicted by scan was inaccurate however it made a significant impact on antenatal care in a good proportion of patients.